Livscykelanalys av produkten Trådlös fiber - Klintgården, Martin (My University, 2017)
Vixor & Co AB is a Gothenburg based company that has been working with wireless communication for the last 20 years. Today they have a product called Wireless Fiber, which essentially is what it sounds like. It is a modern microwave link that can transmit data of up to 12 Gbit/s in a singular network. The goal of this thesis was to assess the environmental impact of each step involved in establishing Vixor’s product Wireless Fiber. This study will then act as a basis for further work within Vixor for a better environment. For assessing the environmental impact the method lifecycle analysis (LCA) was chosen since this method consists of following the product throughout it’s lifetime, often called from cradle to grave. When all the processes with an environmental impact during the establishment of Wireless Fiber have been compiled, their specific impact category needs to be established. For this the well renowned method ReCiPe Midpoint and ReCiPe Endpoint was used. Midpoint consists of 18 impact categories such as Climate change, ozone depletion, human toxicity etc. The database used for quantifying environmental impacts was Ecoinvet 3.3, along with the graphical interface openLCA. Originally the result showed a very large part of the environmental impact coming from the steel involved in building the tower for the microwave link. However, this was deemed a bit skew since the number of products that use the tower was not accounted for. Therefore, the environmental impact from the tower was divided by four to symbolize an average userbase of four products, this resulted in the tower being about 50% of the total impact in ReCiPe Endpoint. A recommendation for lowering the environmental impact is collaboration between Vixor & Co AB and companies responsible for mobile internet, this should be established to maximize usability of each tower. This recommendation was based both on the result of this report as well as the Swedish government’s internet plan Sverige helt uppkopplat 2020. This plan states that mobile internet should be an option for 100% of household situations and microwave link in 50%. Therefore, optimizing the placement of towers to maximize usability for both technologies, would decrease the environmental impact of establishing the government’s plan. A further LCA study to evaluate the differences between conventional fiber cable in the ground and Wireless Fiber, is recommended so that communes and towns have a better understanding when evaluating their options, for reaching the 95% goal of high speed internet within the plan Sverige helt uppkopplat 2020.
Keywords: Naturresursteknik; Hållbar utveckling; Miljöbioteknik; Informations- och kommunikationsteknik; Environmental Engineering; Sustainable Development; Environmental Biotechnology; Information & Communication Technology